2012
DOI: 10.1159/000342806
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin Induces Human Macrophages to Form Intracytoplasmic Vacuoles Mimicking Hofbauer Cells in Human Chorionic Villi

Abstract: The most characteristic morphological feature of macrophages in the stroma of placental villi, known as Hofbauer cells, is their highly vacuolated appearance. They also show positive immunostaining for human chorionic gonadotropin (hCG) and express messenger ribonucleic acid of the luteinizing hormone/chorionic gonadotropin receptor with a deletion of exon 9 (LH/CG-R Δ9). Maternal hCG enters fetal plasma through the mesenchyme of the placental villi and promotes male sexual differentiation in early pregnancy; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In general, hCG has a protective effect on pregnancy and promotes fetal survival by promoting immune tolerance via interaction with macrophages, natural killer cells, and B‐ and T‐lymphocytes. However, in higher doses, hCG may exhibit harmful effects on fetal development and may induce an immune cell response with altered cytokine and reactive oxygen species production, triggering exaggerated sFlt‐1 production and thereby reinforcing the cumulative effect of factors predisposing women to pre‐eclampsia. Alternatively, higher availability of sFlt‐1 and anti‐angiogenic effects characterizing pre‐eclampsia might be due to hCG‐stimulated binding of PlGF to membrane and local circulating receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, hCG has a protective effect on pregnancy and promotes fetal survival by promoting immune tolerance via interaction with macrophages, natural killer cells, and B‐ and T‐lymphocytes. However, in higher doses, hCG may exhibit harmful effects on fetal development and may induce an immune cell response with altered cytokine and reactive oxygen species production, triggering exaggerated sFlt‐1 production and thereby reinforcing the cumulative effect of factors predisposing women to pre‐eclampsia. Alternatively, higher availability of sFlt‐1 and anti‐angiogenic effects characterizing pre‐eclampsia might be due to hCG‐stimulated binding of PlGF to membrane and local circulating receptors.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, Katabuchi and colleagues recently demonstrated that hCG induces transient vacuole formation in human monocytes, morphologically mimicking Hofbauer cells. The authors suggest that Hofbauer cells and especially their vacuoles are involved in the protection of fetal tissue from high amounts of maternal hCG (49). Besides an effect of steroid hormones and gonadotropins on monocytes and macrophages, AFP is suggested to have an influence on both innate immune cell types.…”
Section: Hormonal Influence On Immune Cells During Pregnancymentioning
confidence: 99%
“…They possess a very specific morphology characterized by an occurrence of visible granulose vacuoles. A recent study showed that these vacuoles are a result of exposure to and uptake of β-hCG and that this specific phenotype can also be promoted in other macrophage cell lines by stimulation with β-hCG (18). We and others have shown that HBCs have an M2 anti-inflammatory, regulatory phenotype.…”
Section: Introductionmentioning
confidence: 99%